Κοινωνικοπολιτικές όψεις του γέροντα στις κωμωδίες του Αριστοφάνη - Παυλή, Κέλυ (2020)
The Aristophanic comedy has been relentlessly criticizing the political, social and economic decline of the Athenian democracy, using irony and satire as weapons. The actors of the social critique of the aristophanic comedy in the establishment are the human irony - “Ironics” - and the arrogant elders who, with their flaws, obsessions and their innovative subversive tendencies, imprint on the scene the dysfunctions of the political system and the collective desire for social change. The old comic heroes, sometimes winners and sometimes losers, live and breathe in the unfavorable historical conditions created by the Peloponnesian war, but having experienced as young then, the glorious days of Athenian democracy after the Persian wars. The elders express in all plays the political desires and hopes of the poet and the theatrical audience, for the revival of the decadent socio-political system of the 4th century. In the thesis, using as a basis the typology of the Aristophanic characters, of F. M.Cordford (19141, 1934², 19933) and the distinction of the elders, a) to arrogant elders and b) to ironic elders, we investigate which elders from the beginning adopt and which undermine, the illusion of the established ideological system and in what ways.